Application of Rainfall Prediction Model on Two Rice Production Centers, in West Java - Apriana, Yayan - (Informatika Pertanian, 2015)
The primary objective of this study was to develop rainfall prediction model using artificial neural network analysistechniques, the second objective was to apply the prediction model in rice production centers, and the third objectivewas to compare the model predictions in rice production centers. Research is a desk study with case study in Indramayuand Cianjur districts, West Java. The primary step of this study was collection of rainfall data and map information andClimatology of Rainfall Stations in each district using a combination of input SST Anomaly Nino3.4 and DMI, usingdata from 1990 to 2010, the second step was preparation of rainfall prediction models using network analysis techniquesnerve propagation, the third step was validation the model by comparing the output that has been formed with the actualrainfall data, and the fourth step was comparing rainfall prediction with the results of global climate predictions. Theresults showed that formulation and Validation of the model using input anomalies in the sea surface temperature Nino3.4and DMI applied in Indramayu district was able to follow the actual value of the variability of rainfall, especially duringthe dry season, while in Cianjur district the model was less able to describe it well. The resulting model for Cianjurdistrict validation was low value so it is advisable not to use the model for prediction.